CONCEPTUALIZATION OF THE PRINCIPLES OF MANAGEMENT OF STAFF DEVELOPMENT FOR STRENGTHENING HUMAN POTENTIAL AND ENSURING THE ECONOMIC SECURITY OF THE ENTERPRISE (Development Service Industry Management, 2024)
The article examines theoretical approaches to the management of personnel development to strengthen human potential and ensure the economic security of the enterprise. The generalization and system analysis provided an opportunity to prove that the development and conceptualization of the principles of managing the development of the company's personnel will allow to take into account the assessment of the existing potential and determine the attractors of the company's development.The theoretical and methodological basis of the research is the work of domestic and foreign scientists. The results were obtained due to the application of a system of methods: the method of logical analysis, which made it possible to build the logic of the research; deductions – to identify individual factors that affect personnel development; analysis and synthesis - for the formation of a conceptual approach to improving the management system of personnel development of the enterprise in the structure of a corporate university. The graphic method made it possible to visualize the obtained research results.A critical analysis of existing approaches to determining the components of the personnel development system was conducted, as a result of which the following elements were singled out: the company's personnel policy, personnel administration, personnel reserve formation, personnel attestation, recruitment and selection of employees, personnel planning, personnel adaptation, and employee training. The article substantiates that the optimal way to solve the problems that arise during the functioning of the personnel development system is to create a corporate university of the enterprise.Based on the analysis of the distinctive features of a corporate university and training center, the advantages of creating a corporate university were formed. The effectiveness of the creation and development of a corporate university is proven by the example of successful companies around the world.The authors of the article proposed a conceptual approach to improving the management system of personnel development of the enterprise in the structure of a corporate university, which includes the goals and objectives of personnel development; compliance with the basic principles of personnel development; blocks for choosing models, forms and methods of personnel development; block of formation of the system of managing the development of the personnel of the organization in the structure of the corporate university; modeling block; result block.The obtained conclusions and results of the research will contribute to the strengthening of human potential and ensuring the economic security of the enterprise.
Keywords: personnel; personnel development; mechanism; management; economic security; potential